Scarcity of Safe Drinking Water in the South-West Coastal Bangladesh (Journal of Environmental Science and Natural Resources, 2019)
This study incorporates a detail exploration of drinking water scarcity in the south-western coastal area of Bangladesh. The objectives were to recognize the constraints of potable water supply in the coastal area and to identify the water-scarce area of a coastal community of Bangladesh. Both primary and secondary data have been used to carry out the study. A total of 349 households were selected by using appropriate statistical procedure. ArcGIS has been used for pertinent mapping and calculating the served and unserved (inadequate supply) area of the nearest community water source e.g. pond sand filters or tube-wells. This study found that the root causes i.e. saline water intrusion, reduction of upstream flow, sea level rise, disasters, polder, arsenic contamination, shrimp cultivation in brackish water, excessive use of underground water and lack of appropriate aquifer were highly influential for the disturbance of potable water supply in the coastal area. In addition, it has been showed that about two-third of the settlement areas as well as households fell into the water scarce zone.J. Environ. Sci. & Natural Resources, 11(1-2): 17-25 2018